Asymmetric supercapacitors based on carbon nanofibre and polypyrrole/nanocellulose composite electrodes1. Issue 21 (6th March 2015) - Tammela, Petter; Wang, Zhaohui; Frykstrand, Sara; Zhang, Peng; Sintorn, Ida-Maria; Nyholm, Leif; Strømme, Maria
<x xml:space="preserve">Abstract</x> Asymmetric, all-organic supercapacitors (containing an aqueous electrolyte), exhibiting a capacitance of 25 F g−1 (or 2.3 F cm−2) at a current density of 20 mA cm−2 and a maximum cell voltage of 1.6 V, are presented.